2020
DOI: 10.4014/jmb.2008.08058
|View full text |Cite
|
Sign up to set email alerts
|

Effective Blocking of Microbial Transcriptional Initiation by dCas9-NG-Mediated CRISPR Interference

Abstract: CRISPR interference (CRISPRi) has been developed as a transcriptional control tool by inactivating the DNA cleavage ability of Cas9 nucleases to produce dCas9 (deactivated Cas9), and leaving dCas9 the ability to specifically bind to the target DNA sequence. CRISPR/Cas9 technology has limitations in designing target-specific single-guide RNA (sgRNA) due to the dependence of protospacer adjacent motif (PAM) (5'-NGG) for binding target DNAs. Reportedly, Cas9-NG recognizing 5'-NG as the PAM sequence has been const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To integrate the cas9-NG -KmR cassette in the E. coli genome, we inserted the cas9-NG -KmR cassette using a previously described recombineering technique [ 30 ]. The cas9 gene was codon-optimized using the Codon Optimization Tool ( , accessed on 1 June 2021) to carry seven point mutations (encoding R1335V, L1111R, D1135V, G1218R, E1219F, A1322R, and T1337R) and to be chemically synthesized (Integrated DNA Technologies, Coralville, IA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…To integrate the cas9-NG -KmR cassette in the E. coli genome, we inserted the cas9-NG -KmR cassette using a previously described recombineering technique [ 30 ]. The cas9 gene was codon-optimized using the Codon Optimization Tool ( , accessed on 1 June 2021) to carry seven point mutations (encoding R1335V, L1111R, D1135V, G1218R, E1219F, A1322R, and T1337R) and to be chemically synthesized (Integrated DNA Technologies, Coralville, IA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The P1 vir phage was used to transfer mutations to other strains via standard P1 transduction. The P1 lysates of chloramphenicol-resistant E. coli SH148 cells were used to transduce the HK1160 ( araBAD :: dcas9 - NG -KmR) 40 strain to generate the SH150 strain. Target genes identified from the sgRNA library were knocked out using the following method.…”
Section: Methodsmentioning
confidence: 99%
“…PAM specificity can be indirectly defined through the binding affinity and repression of the target gene using catalytically deactivated Cas9 (dCas9) and dCas9-NG. Previous studies have demonstrated that dCas9 and dCas9-NG are less restricted by PAM requirements, suggesting that target binding and target cleavage are mediated by different mechanisms [ 75 , 76 ].…”
Section: Pam-independent Genome Editingmentioning
confidence: 99%